Indirect computed tomography lymphangiography with aqueous contrast for evaluation of sentinel lymph nodes in dogs with tumors of the head. Issue 5 (21st May 2017) - Grimes, Janet A.; Secrest, Scott A.; Northrup, Nicole C.; Saba, Corey F.; Schmiedt, Chad W.
Abstract: Sentinel lymph node evaluation is widely used in human medicine to evaluate the first lymph node(s) to which a tumor drains. Sentinel lymph node biopsy allows avoidance of extensive lymphadenectomies in cases where the sentinel lymph node is negative for metastasis, thereby reducing patient morbidity. It has been shown that regional lymph nodes are not always the sentinel lymph node, thus identification and sampling of sentinel lymph nodes allows for more accurate staging, which is critical for treatment and prognostication in dogs with cancer. The objective of this prospective, pilot study was to determine if indirect computed tomography (CT) lymphangiography with aqueous contrast agent would successfully allow identification of sentinel lymph nodes in dogs with masses on the head. Eighteen dogs underwent CT lymphangiography. The sentinel lymph node was successfully identified within 3 min of contrast injection in 16 dogs (89%). Compression of lymphatic vessels from endotracheal tube ties and/or the patient's own body weight delayed or prevented identification of sentinel lymph nodes in two dogs (11%). Computed tomography lymphangiography with aqueous contrast can be used successfully to rapidly identify sentinel lymph nodes in dogs with masses on the head.